Return of results in the genomic medicine projects of the eMERGE network - Kullo, Iftikhar J.; Haddad, Ra'ad; Prows, Cynthia A.; Holm, Ingrid; Sanderson, Saskia C.; Garrison, Nanibaa' A.; Sharp, Richard R.; Smith, Maureen E.; Kuivaniemi, Helena; Bottinger, Erwin P.; Connolly, John; Keating, Brendan J.; et al. (Frontiers in Genetics, 2014)
The electronic Medical Records and Genomics (eMERGE) (Phase I) network was established in 2007 to further genomic discovery using biorepositories linked to the electronic health record (EHR). In Phase II, which began in 2011, genomic discovery efforts continue and in addition the network is investigating best practices for implementing genomic medicine for patient care, in particular, the return of genomic results in the EHR for use by physicians at point-of-care. To develop strategies for addressing the challenges of implementing genomic medicine in the clinical setting, the eMERGE network is conducting studies that return clinically-relevant genomic results to research participants and their health care providers. These genomic medicine pilot studies include returning individual genetic variants associated with disease susceptibility or drug response, as well as genetic risk scores for common ‘complex’ disorders. Additionally, as part of a network-wide pharmacogenomics-related project, targeted resequencing of 84 pharmacogenes is being performed and select genotypes of pharmacogenetic relevance are being placed in the EHR to guide individualized drug therapy. Individual sites within the eMERGE network are exploring mechanisms to address incidental findings generated by resequencing of the 84 pharmacogenes. In this paper, we describe studies being conducted within the eMERGE network to develop best practices for integrating genomic findings into the EHR, and the challenges associated with such work.